Hydrogen peroxide-induced mitochondrial DNA deletion in Danio rerio (Dhaka University Journal of Biological Sciences, 2025)
Oxidative stress has profound effect on mitochondrial DNA (mtDNA) and could cause mitochondrial dysfunction if remains unrepaired. Here, we showed that 20 μM H2O2 stress over 96 hours could induce mtDNA deletion in Danio rerio model. Although the fishes did well upon such a challenge with an LC50 value of 257.494 ± 19.434 μM, deletion in their egg mtDNA was observed but degradation was observed for the brain mtDNA. The water quality was not altered with the addition of 20 μM H2O2. We have successfully identified a deleted region of the Danio rerio mtDNA. The estimated size of the deletion was 7124 bp and was observed in both egg and brain mtDNA. We deduced that such deletion could have occurred from a recombination between an inverted repeat pair of Danio rerio mtDNA, and a fusion protein composed of cytochrome c oxidase II and cytochrome b could be generated upon such deletion. Such fusion protein could lead to mitochondrial dysfunction further.Dhaka Univ. J. Biol. Sci. 34(1): 41-50, 2025 (January)